2018
DOI: 10.3390/ma11091681
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Mechanical Properties of a Polymer-Infiltrated Ceramic-Network Material Used for the Fabrication of Hybrid Abutment

Abstract: Polymer-infiltrated ceramic-network (PICN) material is a new type of material used for the hybrid abutments of dental implants. This study aimed to compare flexural strength, bond strengths, and fracture-resistance values of PICN with lithium disilicate ceramic (LDS) and to evaluate the effect of thermocycling on the tested parameters. Twenty specimens were fabricated using computer-aided design and manufacturing (CAD-CAM) technology for each material according to three-point bending (n = 10), microshear bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…In the present study, there were significant differences between the tightening torque and loosening torque, within each group. The thermal aging may have affected the integrity of the resin cement with adverse effect on load transfer [18,19]. Tzannas et al [26] reported that the removal torque is 85 up to 90% of tightening torque.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there were significant differences between the tightening torque and loosening torque, within each group. The thermal aging may have affected the integrity of the resin cement with adverse effect on load transfer [18,19]. Tzannas et al [26] reported that the removal torque is 85 up to 90% of tightening torque.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal aging has been proposed to simulate the extreme conditions commonly experienced in the oral environment [8,10,17]. The thermal aging could induce the degradation of resin cement at the titanium base insert and the ceramic interface that may affect the load transfer at the interface [18,19]. A major challenge today is understanding the response to each restorative material.…”
Section: Introductionmentioning
confidence: 99%
“…In zirconia abutments, however, junctional epithelium was significantly shorter than titanium one-piece abutments [51]. Ongun et al measured the mechanical properties of these hybrid-type abutments including titanium bases, showing that PICN had lower fracture resistance and weaker adhesion to resin cements compared with lithium disilicate ceramic [52]. Such mechanical failure of PICN hybrid-type abutments could also cause the soft tissue seal to break.…”
Section: Materials For Abutmentmentioning
confidence: 99%
“…They highly recommend the use of lithium disilicate ceramics as custom-made hybrid implant abutments regarding their fracture resistance and bond strength. 51 The first null hypothesis stating that the technique of construction would not affect the retention of abutments on Ti-Base was rejected. Lithium disilicate ceramics have been known by two techniques of construction; either by CAD/ CAM or Pressing technology.…”
Section: Discussionmentioning
confidence: 99%